ANALYSIS OF THE DAWN ALMS MOVEMENT ON IMPROVING THE ECONOMIC WELFARE OF THE COMMUNITY IN BANTAN TENGAH VILLAGE, BENGKALIS REGENCY - Munawarah, Faridatul; Ilham, Muhammad; Saifullah (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study aims to analyze the influence of the dawn alms movement on improving the economic welfare of the community in Bantan Tengah Village, Bengkalis Regency. The dawn alms movement is a religious-based social activity that is routinely carried out by the community by setting aside some of their sustenance every morning after the dawn prayer. This study applies a quantitative approach through survey methods and data collection techniques through observation, questionnaires, interviews, and documentation. The results of the study show that the dawn alms movement has a significant effect on increasing the income and expenditure of the beneficiary community. In addition, this movement has also succeeded in increasing social solidarity and the spirit of mutual cooperation in the community. The factors for the success of this program include consistency of implementation, active community involvement, and transparent fund management although there are still some obstacles in the accountability of fund distribution. Thus, the dawn alms movement in Bantan Tengah Village is a form of economic empowerment based on Islamic values ​​and local wisdom that is worthy of continued development.